Radiographic incidental finding of a complex odontoma associated with mandibular third molar agenesis: a rare case report - Alus, Levi Natya; Agustin, Sylvia (Ikatan Radiologi Kedokteran Gigi Indonesia, 2026)
Objectives: This case report is aimed to report radiographic features of complex odontoma with mandibular third molar agenesis an incidental rare case. Case Report: A 22-year-old female presented to the Dental Hospital Mulawarman University with a complaint of pain accompanied by tooth sensitivity in the maxillary molar. Extraoral clinical examination revealed no abnormal findings. Intraoral clinical examination showed a dental restoration on tooth 16. Radiographic findings revealed a radiopaque area suggestive of a restorative material, accompanied by a radiolucent lesion extending from the disto-occlusal region to the pulp chamber of tooth 16. Incidentally, an irregular, well-defined, corticated lesion was observed in the mandible region, associated with the absence of tooth 38. These findings were consistent with a complex odontoma occurring in conjunction with agenesis of the mandible third molar. Conclusion: In this case, unilateral irregular round radiopaque well–defined corticated and the absence of third molar teeth in the mandible were found as the radiographic features that led to the suspect radiodiagnosis of a complex odontoma with agenesis of the third molar.